A comparison of novel electrocautery-enhanced lumen-apposing metal stents and plastic stents in endoscopic ultrasound-guided drainage of infected walled-off necrosis: a multicenter randomized study - Moon, Jong Ho; Park, Se Woo; Lee, Yun Nah; Lee, Sang Hyub; Kim, Seong-Hun; Lee, Dong Wook; Cho, Chang Min; Kim, Sung Bum; Park, Chan Hyuk (Endoscopy, 2024)
Background Although lumen-apposing metal stents (LAMSs) have been increasingly used for walled-off necrosis (WON), their advantages over plastic stents in infected WON are unclear. We investigated the safety and efficacy of a novel electrocautery-enhanced LAMS for managing infected WON.Methods Patients who required endoscopic ultrasound-guided WON drainage were randomly assigned to LAMS or plastic stent groups. The primary outcome was total number of direct endoscopic necrosectomy (DEN) procedures required to achieve clinical success. Secondary outcomes included rates of technical success, clinical success, and adverse events.Results 46 patients were included in the LAMS (n = 23) and plastic stent (n = 23) groups. The median total number of DEN procedures did not differ significantly between the plastic stent group (4 procedures, interquartile range [IQR] 2.5–5.0) and LAMS group (9 procedures, IQR 8.0–9.0) (P = 0.07). The LAMS group demonstrated a significantly higher clinical success rate than the plastic stent group based on intention-to-treat analysis (100% vs. 73.9%, P =0.03) at 8 weeks but not at 4 weeks. Significant bleeding occurred in one patient in the plastic stent group and no patients in the LAMS group.Conclusions We found no significant difference in the total number of DEN procedures between LAMSs and plastic stents for managing infected WON. The only statistically significant finding was a higher clinical success rate at 8 weeks for patients treated with LAMS. The use of LAMS did not result in any adverse events, such as bleeding or buried LAMS syndrome, within the study duration.